2020
DOI: 10.1002/jbio.202000005
|View full text |Cite
|
Sign up to set email alerts
|

Distinguishing metastatic triple‐negative breast cancer from nonmetastatic breast cancer using second harmonic generation imaging and resonance Raman spectroscopy

Abstract: Triple‐negative breast cancer (TNBC) is an aggressive subset of breast cancer that is more common in African‐American and Hispanic women. Early detection followed by intensive treatment is critical to improving poor survival rates. The current standard to diagnose TNBC from histopathology of biopsy samples is invasive and time‐consuming. Imaging methods such as mammography and magnetic resonance (MR) imaging, while covering the entire breast, lack the spatial resolution and specificity to capture the molecular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 71 publications
3
30
0
Order By: Relevance
“…NFL has the potential to be an alternative optical tool for medical armamentarium 59 . Compared to other techniques for detection of metastatic potential of cancer cells such as those by Paidi et al 60 and Bendau et al 61 , the NFL technique can not only be used for measurements with cells in vitro and fresh tissue specimens ex vivo, but also for in vivo measurements. Since it does not involve spatial scanning (mapping), it works faster than those that require mapping 60 , 61 , and can potentially be implemented for real-time diagnosis during surgery.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…NFL has the potential to be an alternative optical tool for medical armamentarium 59 . Compared to other techniques for detection of metastatic potential of cancer cells such as those by Paidi et al 60 and Bendau et al 61 , the NFL technique can not only be used for measurements with cells in vitro and fresh tissue specimens ex vivo, but also for in vivo measurements. Since it does not involve spatial scanning (mapping), it works faster than those that require mapping 60 , 61 , and can potentially be implemented for real-time diagnosis during surgery.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…The SHG image analysis confirmed that literalized and stiffened collagen morphology in 4T1 tumors could be used as a marker for metastatic potential. And the studies also indicated that in vivo SHG imaging and in vitro RRS could distinguish the collagen, molecular and metabolic characteristics between metastatic 4T1 tumors and non‐metastatic 67NR tumors 109 …”
Section: Monitoring Breast Cancer Metastasis By Mpmmentioning
confidence: 92%
“…By using the different fit coefficients for fat and collagen, the authors demonstrated a Raman diagnostic algorithm illustrating 94% sensitivity, 96% specificity, and 86% overall accuracy for detecting infiltrating carcinoma. A range of other studies also demonstrated the potential of Raman spectroscopy in diagnosing breast cancer in human and mouse breast tissues [ 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 ]. By exploiting the fingerprint region of the Raman spectrum and various machine learning techniques, Raman spectroscopy showed diagnostic potential for distinguishing cancerous tissues from normal tissues in brain cancer [ 56 , 97 , 98 , 99 , 100 ], skin cancer [ 42 , 101 , 102 , 103 , 104 , 105 ], gastrointestinal cancer [ 106 , 107 , 108 , 109 ], and lung cancer [ 110 , 111 ].…”
Section: Raman Spectroscopy As a Label-free Tool For Cancer Metabomentioning
confidence: 97%